Incidence and site specific characteristics of angiosarcoma in Japan using a population-based national cancer registry from 2016 to 2019 - Toshiyuki Takemori; Koichi Ogura; Chigusa Morizane; Tomoyuki Satake; Shintaro Iwata; Yu Toda; Shudai Muramatsu; Hiroya Kondo; Eisuke Kobayashi; Takahiro Higashi; Akira Kawai (Scientific Reports)
Abstract Angiosarcoma is so rare, no reports on its epidemiology and prognosis using nationwide population-based data exist. The present study aimed to clarify the characteristics and clinical outcomes of angiosarcoma using the National Cancer Registry (NCR) in Japan. We analyzed data from 23,522 patients with soft-tissue sarcomas (STS), entered in the NCR in 2016–2019 using the International Classification of Diseases-Oncology, Third Edition cancer topography and morphology codes. We extracted demographics, tumor details, treatment, and prognosis for each patient. Of 23,522 STS patients, 1,973 patients were enrolled in the angiosarcoma group and 21,549 in the non-angiosarcoma group. Angiosarcoma accounts for 8.4% of all STS (adjusted incidence: 0.18/100,000/year). Most angiosarcoma patients were men (58.7%) and the most common tumor location was the head/neck (51.0%). In the angiosarcoma group (compared to the non-angiosarcoma group): age at diagnosis was significantly older; more tumors were localized; chemotherapy and radiotherapy were more common; surgery was less common; and the overall survival was significantly worse (P < 0.001). Several factors were associated with worse overall survival in the multivariate analyses. The present study is the first to have clarified the epidemiology, clinical features, treatment, prognosis, and significant factors affecting prognosis of patients with angiosarcoma in Japan.